2016
DOI: 10.1037/pspp0000077
|View full text |Cite
|
Sign up to set email alerts
|

Sexual arousal and masculinity-femininity of women.

Abstract: Studies with volunteers in sexual arousal experiments suggest that women are, on average, physiologically sexually aroused to both male and female sexual stimuli. Lesbians are the exception because they tend to be more aroused to their preferred sex than the other sex, a pattern typically seen in men. A separate research line suggests that lesbians are, on average, more masculine than straight women in their nonsexual behaviors and characteristics. Hence, a common influence could affect the expression of male-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 103 publications
(236 reference statements)
5
35
0
Order By: Relevance
“…men respond most to the same sex, and bisexual men show, on a group level, responses that are in-between those of heterosexual and homosexual men (Bailey, Rieger, & Rosenthal, 2011;Rieger et al, 2013;. In women, both pupil dilation and genital arousal patterns are weakly related to their sexual orientation, largely because heterosexual and bisexual women respond similarly to both sexes, whereas lesbians are somewhat more aroused to their preferred sex (women) than the other sex (Chivers et al, 2007;Rieger, Savin-Williams, Chivers, & Bailey, 2015b).…”
Section: !mentioning
confidence: 98%
See 1 more Smart Citation
“…men respond most to the same sex, and bisexual men show, on a group level, responses that are in-between those of heterosexual and homosexual men (Bailey, Rieger, & Rosenthal, 2011;Rieger et al, 2013;. In women, both pupil dilation and genital arousal patterns are weakly related to their sexual orientation, largely because heterosexual and bisexual women respond similarly to both sexes, whereas lesbians are somewhat more aroused to their preferred sex (women) than the other sex (Chivers et al, 2007;Rieger, Savin-Williams, Chivers, & Bailey, 2015b).…”
Section: !mentioning
confidence: 98%
“…We regressed this contrast onto self-reported sexual orientation. Independent variables included both the linear and quadratic function of sexual orientation because these relations can be, to some degree, curvilinear (Rieger et al, 2013;Rieger et al, 2015b). Figure 1A shows that for men, the linear relationship (but not the curvilinear relationship) of pupil dilation to the same sex or other sex with sexual orientation was significant, p < .0001, β = .54 [.40, .67].…”
Section: Predictionmentioning
confidence: 99%
“…This is supported by evidence that suggests increased attractiveness is associated with increased positive valence as well as positive cognition (Eagly, Ashmore, Makhijani, & Longo, 1991;Langlois et al, 2000;Zebrowitz & Franklin, 2014). Furthermore, it has also been shown that the subjective experience of sexuality and/or sexual orientation does not necessarily dictate the perception of attractiveness (see Rieger, Savin-Williams, Chivers, & Bailey, 2016). Future studies should therefore seek to address whether the affective differences observed towards male and female bodies might be related to how attractive the perceiver reports the body to be.…”
Section: Discussionmentioning
confidence: 89%
“…In general, sex and sexual orientation differences in sexual response are comparable for these measures. Heterosexual men respond substantially more to females than males, and homosexual men respond substantially more to males than females 5 8 ; thus, on average, genital arousal and pupil dilation patterns verify men’s reported sexual orientations.…”
Section: Introductionmentioning
confidence: 84%
“…However, this pattern can vary for genital response, depending on stimulus type 9 . Moreover, for unknown reasons it is stronger if assessed with pupil dilation than genital response 7 , 8 . Pupil dilation is, on average, a valid indicator of sexual response 6 , 7 , 10 , 11 , but it cannot be ruled out that other cognitive or emotional effects distort its precision in this respect 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%